2021
DOI: 10.3390/cancers13092134
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast-Derived IL-6 Determines Unfavorable Prognosis in Cholangiocarcinoma by Affecting Autophagy-Associated Chemoresponse

Abstract: Background: Interleukin-6 (IL-6) released by cancer-associated fibroblasts (CAFs) has been shown to associate with the malignant behavior of cholangiocarcinoma (CCA). Here, we aimed to validate with clinical and molecular data the hypothesis that CAF infiltration and release of IL-6 predict poor prognosis in CCA patients following dysregulation of autophagy in cancer cells. Methods: Stromal IL-6 and cancer-cell-associated autophagy proteins LC3 and p62 were assayed by Tissue MicroArray immunohistochemistry and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 54 publications
8
27
0
Order By: Relevance
“…Interrogation of a TCGA dataset led to the conclusion that patients bearing a tumor with low expression of such Hh/EMT genes along with high expression of the MAP1LC3B gene (suggestive of active autophagy) have a better overall survival and are more responsive to platinum-based therapy. This finding is in agreement with the observation that low expression of IL-6 (indicative of stromal inflammation) along with high expression of LC3 (indicative of active autophagy) in cholangiocarcinomas associates with sensitivity to chemotherapy and better overall patient survival [59].…”
Section: Discussionsupporting
confidence: 92%
“…Interrogation of a TCGA dataset led to the conclusion that patients bearing a tumor with low expression of such Hh/EMT genes along with high expression of the MAP1LC3B gene (suggestive of active autophagy) have a better overall survival and are more responsive to platinum-based therapy. This finding is in agreement with the observation that low expression of IL-6 (indicative of stromal inflammation) along with high expression of LC3 (indicative of active autophagy) in cholangiocarcinomas associates with sensitivity to chemotherapy and better overall patient survival [59].…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al (2019) reported that more than 30% of ARGs were differentially expressed in gliomas, and enrichment analysis showed that the biological process (BP) of these DE-ARGs was related to the assembly of autophagosomes. Thongchot et al (2021) found that the expression of MAP1LC3B (LC3B, an autophagy marker gene) was up-regulated in cholangiocarcinoma and the twoyear overall survival rate of patients with high expression of LC3B was higher than that of patients with low expression of LC3B from the survival curve, although there was no significant difference (p 0.3761) in five-year overall survival between the two groups. As can be seen from our results, most ARGs were up-regulated in cholangiocarcinoma and the main BP was enriched in the assembly of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that aggressive features were related to the expression of autophagy-related proteins. Differently, autophagy could influence patient prognosis via affecting response to chemotherapy [ 31 ]. Interestingly, it was found that p62 positivity was related to shorter DFS and OS in PCC.…”
Section: Discussionmentioning
confidence: 99%